Surface patterning atop poly(methyl methacrylate) - Weng, Yiwei (2016)
Shape memory polymers (SMPs), which are featured by the shape memory effect, belong to a new class of materials that have become popular recently due to their potential applications in fields related to engineering and medicine. Microlens have a wild utilization in many fields, such as, engineering, medicine, robotic, etc. Especially artificial compound eyes have many advantages, such as, a large field of view (FOV), high sensitivity, small volume, and 3D imaging etc. As reported in the literature, fabrication of microlens arrays atop poly(methyl methacrylate) (PMMA) is in a two-step manner, indentation and then followed by immersing into ethanol. Cross-section, 3D profile scanning and projection (optical property) of the obtained microlenses are characterized. In this project, three types of microlens arrays were fabricated. One was fabricated with the same size atop a PMMA plate from same sized indents. As tested, these microlenses have the same focus length. The second sample was manufactured with different sized microlens arrays atop the same kind of PMMA plate. In the third sample, microlens arrays were produced atop a curved PMMA sample. Surface scanning experiment and projection experiment were conducted to test the optical properties of these microlens arrays.